Production and Advertising in a Dynamic Hotelling Monopoly - Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2001)
I characterise the dynamics of capacity accumulation and investment in advertising in a spatial monopoly model, contrasting the socially optimal behavior of a benevolent planner against the behaviour of a profit-maximising monopolist. I show that, in steady state, the monopolist always distorts both kinds of investment as compared to the social optimum, except in a situation where the Ramsey equilibrium prevails under both regimes.
Keywords: 330